najemen sarana dan prasarana dalam pengembangan pembelajaran keterampilan beternak sapi di SLB Darma Putra Semin, Gunungkidul tahun ajaran 2013/2014 - Sri Purwanti; Samidjo Samidjo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The purposes of this research are: 1) to know the plan of infrastructure management in developing skill learning, 2) to get factual description of infrastructure management in developing skill learning breeding cow, 3) information monitoring and evaluate the infrastructure management implementation in developing skill learning cow breed in Special School (SLB) Darma Putra Semin Gunungkidul Regency, D I Yogyakarta. This research uses descriptive qualitative approach. The location of the research is Special School (SLB) Darma Putra Semin Gunungkidul Regency, D I Yogyakarta. The subject of the research is the principal, vice principal in curriculum and teaching department, the infrastructure department, students care department, experts, and teachers. The technique of data collection uses observation technique, interview, and documentation. The data analysis technique uses three ways. They are data reduction, data presentation, and conclusion. This results of the research reference are: 1) the infrastructure management planning in developing skill learning breeding cow of Darma Putra Special School (SLB) Semin Gunungkidul Regency, D I Yogyakarta is arranged in an annual coordination meeting. The meeting is held at the beginning of the school year which is followed by the teachers and employees, experts team, and school committee led by the principal,The investigation calculation plan,  the expense donation, the expense commodity and  distribution  commodity  2  )  the  infrastructure  management  in  developing  skill  learning  breed cow of Darma Putra Special school (SLB) Semin Gunungkidul Regency, D I Yogyakarta, the responsibility of the principal and assisted by all the teachers. Development of skill breeding cow can be implemented optimal supported with adequate facilities and infrastructure. 3) The Infrastructure management in developing learning skills play a role in its easier for teachers who deliver learning materials, facilitate students in developing skills, providing sustenance skills so that children can self in the midst of the society. 4)The result of infrastructure management evaluation is up to normal subnormal children with their weaknesses are actually able to be developed by giving life skill in order to prepare the children early in entering their new world of working in the future.